“Bettonan” Contract in Agricultural Management as Poverty Reduction Efforts From Islamic Law Point of View - Suwardi Suwardi; Muhammad Erfan Muktasim Billah (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
The background of this research is the existence of a "bettonan" contract that occurs among the Indonesian farming community. This contract is carried out with a distribution of 80%:20% of agricultural products; 80% for land owners and 20% for tenant farmers. This contract is a legacy from a long time ago that until now has not been touched by the government, resulting in the absence of regulations. This article tries to explore the legal nature of the “bettonan” contract and whether the distribution is in accordance with justice by considering the obligations of both parties to the contract (land owner and tenant farmers). The results of the study indicate that the "bettonan" contract transaction is in accordance with the concept of Islamic law and is included in the category of musyarakah muzaraah contract, and the distribution of results is in accordance with the principle of justice because the risk of tenant farmers is very small. In the end, this “bettonan” contract really needs to get a touch from the government law because it is very helpful in poverty alleviation efforts.